2019
DOI: 10.1101/759845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing Myocardial Repair with CardioClusters

Abstract: 1Background: Cellular therapy to treat heart failure is an ongoing focus of intense 2 research and development, but progress has been frustratingly slow due to limitations of 3 current approaches. Engineered augmentation of established cellular effectors 4 overcomes impediments, enhancing reparative activity with improved outcomes relative 5 to conventional techniques. Such 'next generation' implementation includes delivery of 6 combinatorial cell populations exerting synergistic effects. Concurrent isolation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 102 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Stem cell spheroids, which are 3D spherical cellular assemblies, have recently garnered much attention as promising avenues for disease modeling, drug discovery, and stem cell therapy (34)(35)(36). Typically generated from 3D cell culture, spheroid-based scaffold-free stem cell therapies can enhance cell survival and differentiation and stimulate the secretion of neurotrophic factors through their biomimetic 3D cell-cell interactions (30,31,37,38). They also allow the injectable delivery of high densities of stem cells at sites of CNS injuries or diseases in an accurate and relatively noninvasive manner, thereby enhancing the therapeutic outcomes of stem cell implantation (29,30,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell spheroids, which are 3D spherical cellular assemblies, have recently garnered much attention as promising avenues for disease modeling, drug discovery, and stem cell therapy (34)(35)(36). Typically generated from 3D cell culture, spheroid-based scaffold-free stem cell therapies can enhance cell survival and differentiation and stimulate the secretion of neurotrophic factors through their biomimetic 3D cell-cell interactions (30,31,37,38). They also allow the injectable delivery of high densities of stem cells at sites of CNS injuries or diseases in an accurate and relatively noninvasive manner, thereby enhancing the therapeutic outcomes of stem cell implantation (29,30,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from engineering pre‐vascularized cardiac engraftment, cell therapy strategy with cell sheets or cell aggregates rather than singularized cells can also boost cell engraft rate and survival rate in injured heart. [ 13,38 ] Preclinical study has shown that MI therapy with hESCs‐derived CMs in non‐human primates has a very low survival rate (7%), which is in part due to the high pressure and continuous contraction of the pumping heart. [ 31 ] Alternatively, cell delivery with cell sheets or cell aggregates can be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Alternatively, cell delivery with cell sheets or cell aggregates can be more effective. [ 13,38 ] We assumed that EVC spheroids may also be superior to EVC single cells in the treatment of myocardial infarction. Our results indicated that to a certain extent, EVC spheroids may be more helpful for cardiac function recovery after injection into infarcted area, which suggested that cell aggregates can be an alternative cell delivery strategy for cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They mainly rely on the cleavage or concealing of the RGD ligands in response to magnetism, [23–25] electrochemical potential, [26] light, [27–31] pH, [32, 33] and enzymes [34, 35] . However, the stem cells harvested by these methods lack the capacity to sense and adhere to the target tissues, therefore requiring further complex modification in vitro to introduce targeted components, such as magnetic nanoparticles (MNPs) [36–41] . The post‐collection modification of cells undoubtedly increases the difficulty of cell manipulation and medical costs.…”
Section: Introductionmentioning
confidence: 99%